New species of Tayloriellina (lichenized Ascomycota, Teloschistaceae) from Bolivia - Wilk, Karina (Phytotaxa, 2023)
A new species is described in the genus Tayloriellina from the Bolivian dry Inter-Andean Valleys. Tayloriellina malmeana sp. nov. is characterized by an orange-yellow to creamy/gray, areolate-subsquamulose to granulose thallus, numerous apothecia with intensive orange discs, which dominate the thallus, and the presence of scarce globose isidia, concolorous with the thallus. The new species forms a sister lineage with T. microphyllina, reflecting their geographic origins in the Americas. Both taxa are easily distinguished by morphology because T. microphyllina produces a well-developed, dark orange thallus, distinct orange soralia, and smaller ascospores. The newly described species is discussed in reference to the poorly known South American species, “Caloplaca” byrsonimae s. lat. and “C.” trabicola.